2022
DOI: 10.3390/vaccines10081322
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Vaccination on Healthcare Worker Infection Rate and Outcome during SARS-CoV-2 Omicron Variant Outbreak in Hong Kong

Abstract: Immune escape is observed with SARS-CoV-2 Omicron (Pango lineage B.1.1.529), the predominant circulating strain worldwide. A booster dose was shown to restore immunity against Omicron infection; however, real-world data comparing mRNA (BNT162b2; Comirnaty) and inactivated vaccines’ (CoronaVac; Sinovac) homologous and heterologous boosting are lacking. A retrospective study was performed to compare the rate and outcome of COVID-19 in healthcare workers (HCWs) with various vaccination regimes during a territory-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Nosocomial infection of nine HCWs was only reported in a COVID-19 outbreak in late 2020 [ 18 ]. In this study, about one-fourth of HCWs were infected in our hospital and the proportion was comparable to a private hospital of 600-bed in Hong Kong [ 28 ]. It is important to explore if the infection control measures remained appropriate to protect our HCWs.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nosocomial infection of nine HCWs was only reported in a COVID-19 outbreak in late 2020 [ 18 ]. In this study, about one-fourth of HCWs were infected in our hospital and the proportion was comparable to a private hospital of 600-bed in Hong Kong [ 28 ]. It is important to explore if the infection control measures remained appropriate to protect our HCWs.…”
Section: Discussionmentioning
confidence: 80%
“…The impact of COVID-19 vaccination on HCW infections during circulation of the SARS-CoV-2 Omicron variant has been reported previously. Using the two-dose BNT162b2 regimen as reference, two-dose CoronaVac recipients had a significantly higher risk of infection, whereas three-dose BNT162b2 and two-dose CoronaVac plus BNT162b2 booster regimens were associated with a lower risk of infection [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a retrospective study that evaluated the rate and outcome of COVID-19 in healthcare workers with various vaccination regimens during the omicron BA.2.2 outbreak in Hong Kong showed that using two-dose Comirnaty as a reference, two-dose CoronaVac recipients had a significantly higher risk of being infected (HR=1.69, p <0.0001). Three-dose Comirnaty (HR=0.4778, p <0.0001) and two-dose CoronaVac + Comirnaty booster (HR=0.4862, p =0.0157) were associated with a lower risk of infection ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that extended and strictly enforced quarantine restrictions may place a significant financial, social, and emotional strain on the general population once the universal immunization program has been completed [ 24 , 25 , 26 ]. In light of the fact that a number of research papers have demonstrated that COVID-19 infections can be avoided by receiving vaccinations at the appropriate intervals [ 27 , 28 ], in order to effectively combat this viral illness, it is necessary to take into account the degree to which individuals have developed an immunity to COVID-19 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%